Mesenchymal stem cells modified with angiotensin-converting enzyme 2 are superior for amelioration of glomerular fibrosis in diabetic nephropathy. (April 2020) - Liu, Qingzhen; Lv, Shasha; Liu, Jiaxi; Liu, Shanshan; Wang, Yinghui; Liu, Gang
Highlights: MSCs transduced with the ACE2 gene had a high transduction efficiency. After transplantation, MSC-ACE2 targeted and enhanced local expression of ACE2. MSCs-ACE2 had additional benefits to the progression of DN in vivo and in vitro. The mechanism was to inhibit renal RAS activation and reduce glomerular fibrosis. Abstract: Aims: This study aimed to detect the effect of angiotensin-converting enzyme (ACE) 2-modified mesenchymal stem cells (MSCs) on glomerular fibrosis in vitro and in vivo and investigate the underlying molecular mechanism. Methods: MSCs transduced with the ACE2 gene (MSCs-ACE2) were cocultured with glomerular mesangial cells (GMCs) following Ang II stimulation. MSCs-ACE2 were transplanted into streptozotocin-induced diabetic rats. Physical, biochemical and morphological parameters were measured, and fibrotic indicators and renin-angiotensin system (RAS) components in GMCs and kidney tissues were assessed. Results: The transduction efficiency of MSCs was as high as 85%. The modified MSCs secreted soluble ACE2 protein into the culture medium. After transplantation into rats with diabetes, MSCs-ACE2 targeted injured kidneys and enhanced local expression of ACE2. Compared with MSC treatment alone, MSC-ACE2 treatment was superior in reducing albuminuria and improving glomerulosclerosis. In vitro and in vivo, MSCs-ACE2 were more beneficial than MSCs alone in decreasing Ang II and increasing Ang1–7, thereby inhibiting the detrimental effects of Ang II accumulation by downregulating collagen I and fibronectin (FN) expression and inhibiting the transforming growth factor (TGF-β)/Smad pathway. Conclusions: MSCs modified with ACE2 therapy have additional benefits to the progression of diabetic nephropathy (DN) by inhibiting renal RAS activation and reducing glomerular fibrosis.